Modeling and Simulation of Nonvolatile Memory Based on Copper Sulfide - Khalid Khaleel Mohammad (Tikrit Journal of Engineering Sciences, 2016)
The memory cells has become one of the computer basics electronic components, especially nonvolatile ion-dependent growth of filament or so called Conductive Bridge Random Access Memory (CBRAM) type. The memory cells in this work is focused on using copper sulfide as ionic compound Cu2S, the model proposed to identify the behavior of the cell in terms of voltage and current. The model cell is then simulated in order to extract the variables that affect the behavior of the cell and the factors which can be identify the optimal dimensions and specifications in terms of their small size and minimum power dissipation as possible at the same time. The simulation results show that the best thickness of the cell is about 20 nm with a radius equal to 10 nm, These dimensions of the cell has a resistance ratio of  high resistance state HRS to low resistance state LRS(Roff / Ron) which correspond to different logic is about  1014 .